Retinoblastoma. Part 2. Treatment strategies for intraocular retinoblastoma - S.V. Ivanova; S.A. Kuleva; N.N. Sadovnikova; M.I. Komissarov; M.N. Chistyakova; A.V. Khokhlova; N.A. Shchegoleva (РМЖ "Клиническая офтальмология")
S.V. Ivanova1, S.A. Kuleva1, N.N. Sadovnikova2, M.I. Komissarov2, M.N. Chistyakova2,  A.V. Khokhlova1, N.A. Shchegoleva3 1N.N. Petrov National Medical Research Center of Oncology, St. Petersburg,   Russian Federation 2St. Petersburg State Pediatric Medical University, St. Petersburg, Russian Federation 3K.A. Rauchfuss St. Petersburg Children’s City Multidisciplinary Clinical Center of High Medical Technologies, St. Petersburg, Russian Federation Retinoblastoma is one of the most common retinal tumors in young children. Current early diagnostic and treatment strategies focus on the possibility to implement eye-preserving therapies. The 5-year overall survival for children with retinoblastoma is now 100%. First-line eye removal is recommended in extensive intraocular seeding and poor visual prognosis. The volume of adjuvant therapy is based on the histological risk factors for disease progression. This paper discusses the algorithms to determine risk factors and further systemic treatment strategy in several large study groups. Eye and even vision preservation is now possible in at least 65–75% of retinoblastoma patients. The paper also describes in detail the methods of locally administering chemotherapy which are considered eye-preserving treatment options, i.e., selective intra-arterial chemotherapy and intravitreal chemotherapy. Various physical methods of eye-preserving treatment which underwent significant deve lopment over the past decade are highlighted. In conclusion, the authors emphasize that retinoblastoma survivors, their siblings and offspring should be carefully monitored. Keywords: children, retinoblastoma, enucleation, polychemotherapy, selective intra-arterial chemotherapy, intravitreal chemotherapy, laser photocoagulation, transpupillary thermotherapy, cryotherapy, brachytherapy, monitoring. For citation: Ivanova S.V., Kuleva S.A., Sadovnikova N.N. et al. Retinoblastoma. Part 2.  Treatment strategies for intraocular retinoblastoma. Russian Journal of Clinical Ophthalmology. 2020;20(4):197–203. DOI: 10.32364/2311-7729-2020-20-4-197-203.